The USE OF LITERATURE CIRCLE IN TEACHING READING FOR YOUNG LEARNERS - Novasyari, Ressy (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2021)
This article describes about the concept of Literature circle in teaching reading for young learners. Many people agree that English has a great important as one of International languages. It is taught almost in all levels of education in the world, including Indonesia. Students need to master the four English language skills :litening, speaking, writing and reading. Reading is one of skilss for students acquire. There are some reasons why the students have difficulties in reading such as they are unfamiliar with the vocabulary, they can’t understand the topic of the reading and the teaching method used by the teacher do not attract them. As teachers, we should have new method in teaching and learning process. Literature circle is a good method to support, facilitate and persuade students to enjoy learning English. This method provides students to work with team or make a group discussion who are reading the same work of literature and also students have responsibilities during the discussion sessions in order the students enlarge their knowledge from story that they read.